2007
DOI: 10.1679/aohc.70.243
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of type IV collagen .ALPHA. chains in the mouse ovary and its correlation with follicular development

Abstract: The present study aims to identify alpha chains of type IV collagen in the basement membrane of the mouse ovarian follicle and examine their changes during follicular development using immunofluorescence microscopy with specific monoclonal antibodies. The basement membrane of the serous mesothelium enveloping the ovary contained all alpha chains of type IV collagen, alpha1(IV) through alpha6(IV) chains. Primordial follicles showed a distinct immunoreactivity against all six alpha chains in their basement membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 21 publications
10
22
0
Order By: Relevance
“…increases in Col1a2, Col4a4, Col3a1, and Col6a1 and decreases in Col4a6 and Col4a5) in preovulatory Inha Ϫ/Ϫ granulosa cells. It has been reported that collagen type IV chains-␣3 to -␣6 in the basal lamina decline during follicle growth (57,58), and in Inha Ϫ/Ϫ , these appear to be overexpressed compared with WT. How changes in collagen composition affect the phenotype of Inha Ϫ/Ϫ or contribute to alterations in Inha Ϫ/Ϫ gene expression is currently unknown.…”
Section: Discussionmentioning
confidence: 97%
“…increases in Col1a2, Col4a4, Col3a1, and Col6a1 and decreases in Col4a6 and Col4a5) in preovulatory Inha Ϫ/Ϫ granulosa cells. It has been reported that collagen type IV chains-␣3 to -␣6 in the basal lamina decline during follicle growth (57,58), and in Inha Ϫ/Ϫ , these appear to be overexpressed compared with WT. How changes in collagen composition affect the phenotype of Inha Ϫ/Ϫ or contribute to alterations in Inha Ϫ/Ϫ gene expression is currently unknown.…”
Section: Discussionmentioning
confidence: 97%
“…Previous study demonstrated that signaling through adhesion molecules such as collagen increased FSH receptor expression and progesterone production in granulosa cells from immature porcine ovarian follicles [34]. Nakano et al reported that the granulosa cell layer of the mouse ovarian follicle has a basement membrane like matrix containing Col4A1, Col4A2, Col4A5, Col4A6, and the expression of type IV collagen shows the decreasing trend in mouse follicular development [35]. Here we found that the expression pattern of Col4A1 was consistent with mir-29a expression with FSH treatment broadly.…”
Section: Discussionmentioning
confidence: 99%
“…5, some collagen type IV a-chains were immunohistochemically examined to reveal any changes in the major components of the basement membranes (Rodgers et al 1998, Nakano et al 2007). However, no apparent differences in the collagen a-chains were observed in the antral follicles between the PCO model and control mice (Fig.…”
Section: Histological Examination Of Mouse Ovaries After Injection Ofmentioning
confidence: 99%